The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.mad.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative approaches to facilitate the discovery of prolongevity interventions: Effects of tocopherols on lifespan of three invertebrate species

Abstract: SummaryMany compounds hold promise for pharmacologic manipulation of aging. However, such claims are difficult to investigate due to time and budget constraints. Here, we took a comparative approach, using short-lived invertebrate species, to directly test the effects of two tocopherols (vitamin E) on longevity. γ-tocopherol represents the most abundant tocopherol in the Western diet, while α-tocopherol is selectively enriched in human plasma. Both isoforms demonstrate antioxidant activity and are proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…1a-d). The base and DR diets used here are routinely employed in aging intervention and DR studies in D. melanogaster (Bross et al 2005;Bass et al 2007a;Zou et al 2007). Our findings suggest that supplementation of resveratrol at up to 200 μM is not sufficient to promote longevity of flies under standard or restricted dietary conditions.…”
Section: Resultsmentioning
confidence: 99%
“…1a-d). The base and DR diets used here are routinely employed in aging intervention and DR studies in D. melanogaster (Bross et al 2005;Bass et al 2007a;Zou et al 2007). Our findings suggest that supplementation of resveratrol at up to 200 μM is not sufficient to promote longevity of flies under standard or restricted dietary conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, vitamin E supplementation may indeed quench ROS and reduce oxidative stress, but this may have no or little impact on aging and life span if the importance of these processes has been overestimated in vivo. 17 Secondly, Vitamin E may scavenge ROS, and ROS may be important in the aging process, but this effect might be offset by a parallel compensating impacts on the endogenous antioxidant system, or indeed on any system involved in redox status or oxidative damage, similar to those reported following vitamin C supplementation. 25,26 Thirdly, because body mass and energy metabolism affect both free-radical production and life span, 7,27,28 if vitamin E supplementation influences one or both of these factors, this could offset any potential benefits.…”
Section: Introduction Imentioning
confidence: 98%
“…11 The effects on life span following vitamin E supplementation in animal models are similarly confused. Using a comparative approach, Zou et al 17 reported that ␥-tocopherol, but not ␣-tocopherol, extended life span in Caenorhabditis elegans, but that neither isoform had any life span effect in Drosophila melanogastor or Anastrepha ludens. An increase in median/mean life span has been reported in various strains of mice following vitamin E supplementation [18][19][20][21] or following supplementation with a mixed antioxidant diet containing vitamins E and C. 22 However, other studies report no effect on life span or on oxidative stress following vitamin E supplementation or when using a mixed antioxidant diet.…”
Section: Introduction Imentioning
confidence: 99%
“…1 Flies exhibit a short generation time and high fecundity and have a well-differentiated central nervous system, cardiac anatomy, malphigian tubules (mammalian kidney analogs), and fat body (mammalian adipose tissue analogs). [2][3][4][5][6][7] Also, the ease of inducing gene knockouts and mutagenesis has rendered D. melanogaster as a powerful model to pursue demographic studies on various metabolic disorders. 8 Although rearing flies is a relatively simple process, it requires knowledge of the appropriate individual components in media formulation.…”
Section: Introductionmentioning
confidence: 99%